Drosophila Dscam is an axon guidance receptor exhibiting extraordinary molecular diversity. - Schmucker, D.; Clemens, J.C.; Shu, H.; Worby, C.A.; Xiao, J.; Muda, M.; Dixon, J.E.; Zipursky, S.L. (Cell, 2000)
A Drosophila homolog of human Down syndrome cell adhesion molecule (DSCAM), an immunoglobulin superfamily member, was isolated by its affinity to Dock, an SH3/SH2 adaptor protein required for axon guidance. Dscam binds directly to both Dock's SH2 and SH3 domains. Genetic studies revealed that Dscam, Dock and Pak, a serine/threonine kinase, act together to direct pathfinding of Bolwig's nerve, containing a subclass of sensory axons, to an intermediate target in the embryo. Dscam also is required for the formation of axon pathways in the embryonic central nervous system. cDNA and genomic analyses reveal the existence of multiple forms of Dscam with a conserved architecture containing variable Ig and transmembrane domains. Alternative splicing can potentially generate more than 38,000 Dscam isoforms. This molecular diversity may contribute to the specificity of neuronal connectivity.